The Effectiveness of Students’ Worksheet Based on Multiple Representations to Increase Creative Thinking Skills - Nur Balqis Mutia; Zuhdan Kun Prasetyo (Journal of Education and Learning (EduLearn), 2018)
This research aimed to analyze the effectivity of students’ worksheet based on multiple representation in order to increase creative thinking skills for second years students of junior high school. It used quasi-experiment with nonequivalent control group design. The population of this research was students of class VII SMPN 3 Langsa, academic year of 2017/2018. Then, the samples were students of class VII-1 and VII-2 elected using simple random sampling method. Basically, the effectivity can be seen from students’ creative thinking skills analyzed by using average n-gain and independent sample T test. Furthermore, the result showed that there was an average difference for n-gain and significant score between control class and experiment class. Therefore, the students’ worksheet based on multiple representations can be used for increasing creative thinking skills of students.